Non-HFE hemochromatosis: a case report - Martínez-Ávila, María Cristina (2021)
Hereditary hemochromatosis (HH) consists of a progressive iron overload that leads to an abnormal accumulation of iron in different target organs; and, if not treated in time, can cause multi-organ dysfunction. Various genetic mutations associated with HH have been described, the most frequent is associated with the HFE-gene, which is found in 90% of cases. At present, therapeutic phlebotomy continues to be the treatment of choice for the management of this pathology. We report the case of a patient under follow-up for severe liver fibrosis, with persistence of a high ferrokinetic profile, who five years later was diagnosed with HH not associated to a mutation in the HFE-gene; He was managed with periodic phlebotomies, rapidly presenting a significant clinical improvement and decrease of ferritin levels.